PENGEMBANGAN BUKU SAKU PRAKTIS HADITS ARBA’IN KARANGAN IMAM AN-NAWAWI UNTUK KEMAMPUAN MENGHAFAL HADITS ARBA’IN ( STUDY PADA SANTRI PONDOK PESANTREN SYAFA’ATURRRASUL 2 PUTRA KABUPATEN KUANTAN SINGINGI PROVINSI RIAU) - Firmansyah Firmansyah; Helbi Akbar; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
Based on these problems, this study aims to determine the validity and responses of students to the practical pocket book of arba'in hadith written by Imam An-Nawawi which was developed at the Syafa'turrasul 2 Putra Islamic Boarding School. This type of research is research and development with the development process referring to the 4-D development model. The data collection instrument used was a validation sheet. The data analysis technique used is by calculating the percentage score of the validation assessment. The results showed that the practical pocket book of arba'in hadith written by Imam an-Nawawi that was developed met the valid/feasible category of 3 material experts at 93.93% and 3 media experts at 82.81%. This learning media also meets the valid/feasible category of student responses with a percentage of 89.09%. Based on this assessment, the practical pocket book of arba'in hadith written by Imam an-Nawawi is suitable for use.